Penerapan E-Billing System Untuk Meningkatkan Layanan Air Minum di Desa Cumedak Kecamatan Sumberjambe, Jember - Rusdiana Setyaningtyas; Lutfi Ali Muharom (Indonesian Journal Publisher, 2022)
The partner of this community development program is the Tirta Melati Water Supply and Sanitation System Management Group (KPSPAMS) in Cumedak Village, Sumberjambe District, Jember. The problems faced by partners are: the organization of the customer database has not been carried out in an orderly and systematic manner, didn’t yet have a computer application for financial administration, and payment of drinking water account bills was still carried out conventionally, customers came to the office or the management came to the customers to collect the bills. The program's objective is to improve rural water supply services through orderly administration and an e-billing system, with the output that partners are able to create customer databases and financial reports using computer applications so that they can improve their performance in terms of providing decent and safe drinking water services for the community. The target is that partners become more credible and can compete with similar businesses (e.g. PDAM), and are able to increase the speed and ease of the process of paying customer water bills. The methods used are socialization on institutional strengthening, management and administration, training on computer applications for customer administration and e-billing systems in the process of paying customer water bills, and direct assistance to partners in using computer applications for customer administration and financial reports until they can do it independently. This program results in (1) Partners are able to organize customer databases using computer applications, (2). Partners are able to make financial reports using computer applications, and (3). Partners are starting to implement an e-billing system as a method of paying bills for drinking water accounts that is easy, fast and transparent.